Gastrointestinal side effects in hepatocellular carcinoma patients receiving transarterial chemoembolization: a meta-analysis of 81 studies and 9495 patients - Nathalie Arendt; Maria Kopsida; Jaafar Khaled; Markus Sjöblom; Femke Heindryckx (Therapeutic Advances in Medical Oncology)
Background: Transarterial chemoembolization (TACE) is a widely used treatment for hepatocellular carcinoma (HCC), combining targeted chemotherapy and embolization. While effective, TACE can be associated with significant gastrointestinal (GI) side effects, impacting a patient’s quality of life. Objectives: Quantify the prevalence of key GI complications (diarrhea, nausea, GI toxicity, abdominal pain) following TACE. Design: Systematic review was performed following Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines, focusing on studies that reported side effects of TACE. Studies not involving cTACE or drug-eluting bead TACE (DEB-TACE), non-HCC studies, meta-analyses or systematic reviews, and inaccessible publications were excluded. Data sources and methods: A PubMed search for clinical and randomized trials was conducted. Extracted data included study identifiers, demographics, TACE details, and GI side effect prevalences. The Mixed Methods Appraisal Tool assessed study quality and bias. Results: The analysis included data from 81 studies with 121 individual study arms and 9495 patients. Diarrhea was reported in 38 studies, with a mean prevalence of 23.46% (2.5; 95% confidence interval (CI): 18.39–28.544) and a weighted prevalence of 23.5%. Nausea was most frequently reported, mentioned in 67 studies, with a mean prevalence of 34.66% (2.4; 95% CI: 29.89–39.44) and a weighted prevalence of 32.5%. Abdominal pain was reported in 59 studies, with the highest mean prevalence of 48.07% (2.9; 95% CI: 42.20–53.93) and a weighted prevalence of 46.1%. GI toxicity was reported in 32 studies, with a mean prevalence of 8.85% (1.4; 95% CI: 5.99–11.70) and a weighted prevalence of 9.9%. DEB-TACE generally led to slightly higher rates of nausea, diarrhea, abdominal pain, and GI toxicity compared to conventional TACE. The type of chemotherapy agent influenced prevalence of GI-side effects, with high prevalences observed for agents such as zinostatin and cisplatin. Conclusion: This meta-analysis synthesizes current evidence on managing GI side effects in TACE. Standardizing reporting and developing effective management strategies are crucial to improving patient outcomes.